Towards a universal cortical tau sampling mask. (31st December 2021) - Dore, Vincent; Bohorquez, Sandra Sanabria; Leuzy, Antoine; Shimada, Hitoshi; Bullich, Santiago; Bourgeat, Pierrick; Burnham, Samantha C; Huang, Kun; Krishnadas, Natasha; Fripp, Jurgen; Takado, Yuhei; Stephens, Andrew W; et al.
Abstract: Background: The introduction of the AT(N) framework raised several issues in regards to the definition of T+. What brain regions should be sampled? Based on one or on multiple tracers? In this work, we developed a "universal" cortical tau mask for the AD continuum derived from all the major tau ligands. This "universal" cortical mask will serve as the common tau area for all tracers over which several different regional sampling VOI or composites can be then applied. Guaranteeing sampling of the same common regions is the first step to develop a common scale for all tau tracers: the CenTauR. Method: 464 participants underwent tau scans with either 18 F‐AV1451 (CN=54/AD=24), 18 F‐MK6240 (CN=157/AD=22), 18 F‐PI2620 (CN=10/AD=21), 18 F‐PM‐PBB3 (CN=30/AD=28), 18 F‐GTP1 (CN=15/AD=38) or 18 F‐RO948 (CN=35/AD=30). All CN were Aß‐ and all AD were Aß+. The tau scans were spatially normalized using CapAIBL and the cerebellar cortex was used as reference region. For each tracer, a difference image between the means of the Aß‐ CN and Aß+ AD patients was generated. Difference images were subsequently thresholded at 1/3 of the difference between Aß‐ CN and Aß+ AD in the inferior temporal lobe. A single tau specific mask was then constructed from the intersection of all the specific tau tracer masks. A MRI‐derived grey matter mask at PET resolution was applied to the composite mask only sampling grey matter regions. Finally, the mask was mirrored and fused to remove the hemispherical asymmetry of tau pathology. Agreement between masks was assessed by dice‐scores. Result: Visually, all the tracer‐specific masks appeared very similar. None of the known off‐target binding regions were discernible in the resulting masks (Figure 1). There was good agreement between all masks, with dice‐scores of 0.60 and 0.66 for cortical regions. Conclusion: We constructed an "universal" tau mask for the AD continuum based on all the commonly used tau tracers aiming at standardizing tau sampling and quantification across tracers and across centres. The "universal" tau mask demarcates a tau specific space that can then be sub‐segmented into smaller regions to focus on specific areas or composite regions that might better capture early tau deposition and spreading.